The Role of Social Support in Sustaining Women’s Dual Roles: Empirical Evidence from Bandung, Indonesia - Bambang Rustanto; Edi Suhanda; Tuti Kartika; Aryohaji Istyawan; Pribowo (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Women who simultaneously assume dual roles as employees and household managers face complex social and structural pressures, particularly in urban areas such as Dago Subdistrict, Bandung City. Spousal social support serves as a crucial factor in sustaining the continuity of these dual roles. This study aims to identify the forms and intensity of social support provided by husbands to their wives within the context of dual-role management. A descriptive survey was conducted involving 50 married working women, selected through a two-stage cluster random sampling technique across five neighborhood units (RW), complemented by in-depth interviews with five husband–wife pairs using purposive sampling. The findings indicate that most husbands provide a high level of social support, encompassing emotional, instrumental, informational, and appraisal dimensions. Such support plays a significant role in reducing role conflict, strengthening psychological resilience, and enhancing women’s adaptive capacity in balancing domestic and public responsibilities. In conclusion, the active involvement of husbands reflects a shift toward a more egalitarian household partnership model, contributing to well-being and fostering family resilience.